Exposure to GABAA Receptor Antagonist Picrotoxin in Pregnant Mice Causes Autism-Like Behaviors and Aberrant Gene Expression in Offspring - Kotajima-Murakami, Hiroko; Hagihara, Hideo; Sato, Atsushi; Hagino, Yoko; Tanaka, Miho; Katoh, Yoshihisa; Nishito, Yasumasa; Takamatsu, Yukio; Uchino, Shigeo; Miyakawa, Tsuyoshi; Ikeda, Kazutaka (Frontiers in Psychiatry, 2022)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder that is characterized by impairments in social interaction and restricted/repetitive behaviors. The inhibitory neurotransmitter gamma-aminobutyric acid (GABA) through GABAA receptor signaling in the immature brain plays a key role in the development of neuronal circuits. Excitatory/inhibitory imbalance in the mature brain has been investigated as a pathophysiological mechanism of ASD. However, unclear are whether and how disturbances of GABA signaling in embryos that are caused by GABAA receptor inhibitors cause ASD-like behaviors. The present study examined whether excitatory/inhibitory imbalance during the prenatal period that is elicited by the GABAA receptor antagonist picrotoxin causes ASD-like pathophysiology in offspring. Pregnant mice received picrotoxin or vehicle at 12.5 days of gestation, and offspring were used in behavioral and gene expression analyses. We assessed body maturation, motor function, sociability, repetitive behaviors, open field activity, and anxiety-like behavior. We also analyzed gene expression in the whole brain in male mice using microarrays. Male mice that were prenatally exposed to picrotoxin exhibited a reduction of active interaction time in the social interaction test in both adolescence and adulthood. The gene expression analyses showed that picrotoxin-exposed male mice exhibited a significant increase in the gene expression of odorant receptors. Weighted gene co-expression network analysis showed a strong correlation between social interaction and enrichment of the “odorant binding” pathway gene module. These results suggest that exposure to a GABAA receptor inhibitor during the embryonic period induces ASD-like behavior in offspring. The prenatal inhibition of GABAA signaling may be a novel mechanism that contributes to ASD.